An estimation of the effect of 100% Compliance with Diabetes Treatment: Can we reduce cost of illness with higher compliance rates? - Guvenc Kockaya; Albert I. Wertheimer (University of Minnesota Libraries Publishing, 2011)
Introduction: The current study was designed to estimate the direct cost of noncompliance of diabetes patients to the US health system. Understanding these expenses can inform screening and education budget policy regarding expenditure levels that can be calculated to be cost-beneficial. Materials and Method: The study was conducted in three parts. First, a computer search of National Institutes of Health websites and professional society websites for organizations with members that treat diabetes, and a PubMed search were performed to obtain the numbers required for calculations. Second, formulas were developed to estimate the risk of non-compliance and undiagnosed diabetes. Third, risk calculations were performed using the information obtained in part one and the formulas developed in part two. Results: Direct risk reduction for diabetes-related kidney disease, stroke, heart disease, and amputation were estimated for 100% compliance with diabetes treatment. Risk, case and yearly cost reduction calculated for a 100% compliance with diabetes treatment were 13.6%, 0.9 million and US$ 9.3 billion, respectively. Conclusion: Society, insurers, policy makers and other stakeholders could invest up to these amounts in screening, education and prevention efforts in an effort to reduce these costly and traumatic sequelae of noncompliant diabetes patients.   Type: Original Research